From laws to liturgy : an idealist theology of creation - Epsen, Edward (Studies in Systematic Theology, 2020)
"In From Laws to Liturgy, Edward Epsen offers a constructive account of what God produces in the act of creation and how it is ontologically ordered and governed. Inspired by the philosophy of Bishop Berkeley (18th century), Epsen proposes that the physical world is produced by the way God ordains the course of possible human sensations, with angels executing the divine ordinances. Idealism is here re-attached to a tradition of Christian Platonism, updating the traditional notions of the aeon, angelic government, and the divine ideas, so as to be capable of explanatory work in regard to the philosophical problems of perception and induction: the objectivity and observability of the world are explained by a unified sacramental economy of the Eucharist".